Out-of-hospital cardiac arrest attended by the sports professional: Recommendations for intervention and training in coexistence with COVID-19 - Aranda-García, S. (Apunts Medicina de l'Esport, 2021)
The aim is to promote a safer intervention in a cardiac arrest assisted by a sports pro-fessional during the current pandemic conditions due to COVID-19. The European Resuscitation Council protocol for lay people is adequate for this group, but it must be complemented with the use of personal protective equipment (PPE) adapted to sports professionals. The adaptations of action with respect to the 2015 practical guidelines are: assessment of breathing visually with-out opening the victim`s airways, placement of a mask (preferably > FFP2) on the victim beforestarting resuscitation, resuscitation only with chest compressions except for of children and drowned-cohabitant, and the use of PPE for the sports field of easy learning and greater safety against possible transmission of COVID-19 by drops/aerosols (FFP3, glasses, gloves). These con-siderations should be included in the training/re-training of sports professionals in resuscitation and sports entities should favour the availability of aforementioned PPE.